Contamination of Organ Donor Transport Media With Enteric Flora Predicts Clinically Significant Transplant Site Infections. (August 2017) - Shahrestani, Sara; Goire, Namraj; Robertson, Paul; Kable, Kathy; O'Connell, Phil; de Roo, Ronald; Pleass, Henry C.; Hawthorne, Wayne J.
Abstract : Introduction: The routine culture of organ donor transport media (ODTM) is yet to become standard policy at all transplant centers. This is possibly due to most previous studies finding it is characterized by low culture rates and unclear clinical utility. Our aim was to review our data from bacterial cultures of all ODTM to identify key factors that may contribute to potential infections in transplant recipients. Methods: We reviewed 457 recipients of kidney, pancreas or SPK transplants, of which 286 had cultures performed on ODTM, using sterile technique. 208 samples were transferred into standard culture pots and 95 into BACTEC culture pots. Culture results were reviewed and organisms classified by likely source (skin flora, enteric flora or respiratory/oral flora). We then reviewed the presence of any clinically significant infection at the transplant site in all recipients and characterized the organisms by likely source. Analysis with SPSS statistical package was performed to assess the rate of contamination by source for kidney or SPK transplants and ascertain the likelihood of correspondence in infection source. Results: The sensitivity of BACTEC culture was significantly superior to standard culture (X2(1, 286) =74.06, p<0.001), detecting contamination in 62.1% of samples. This was relative to 15.9% of samples in the standard culture. The increased rate of contamination in the kidney for SPK group over the kidney for kidney alone group was driven by the high rate of enteric flora contamination in the SPK group (26.5%, N=9/34), over kidney for kidney alone transplant (9.8%, N=6/61). This is particularly relevant given 38.5% (10/26) of recipients with enteric flora contamination of transport media had an infection of the transplant site caused by enteric flora. Only 25% (65/260) of recipients who did not have contamination with enteric flora had an infection of the transplant site caused by enteric flora. Conclusions: BACTEC culture is significantly superior and should be adopted as the standard of culture at all transplant centers, to improve the utility of routine testing of ODTM. Evidence suggests transmissibility of enteric contamination of ODTM, and the SPK transplant group is particularly vulnerable in this regard.